Outcomes of Anterior Cruciate Ligament Reconstruction in Obese and Overweight Patients: A Systematic Review. Issue 4 (July 2019) - DiSilvestro, Kevin J.; Jauregui, Julio J.; Glazier, Elizabeth; Cherkalin, Denis; Bennett, Craig H.; Packer, Jonathan D.; Henn, Ralph Frank
Abstract : Objective: To evaluate the mechanism of injury, outcomes, and complications of anterior cruciate ligament (ACL) reconstruction in overweight and obese patients. Data Sources: MEDLINE, EMBASE, and OVID electronic libraries were systematically searched from inception to December, 2017 for any eligible articles using a combination of the phrases "anterior cruciate ligament, " "ACL, " "overweight, " "obese, " and "BMI." Results: Studies that evaluated patients with primary ACL reconstruction, classified patients as overweight or obese, and reported a minimum of 1-year follow-up data were included. Eight cohorts from 9 studies fulfilled the inclusion criteria. There were no significant differences for mechanism of injury, Lysholm scores, Knee injury and Osteoarthritis Outcome Scores values, or return to sports with a body mass index (BMI) above or below 25 kg/m 2 . A significant difference was described in International Knee Documentation Committee (IKDC) scores when comparing obese patients (BMI >30 kg/m 2 ) to patients with BMI <25 kg/m 2 ( P <0.01). In patients with BMI >25 kg/m 2, the risk for arthritis was significantly higher but the risk for revision surgery or contralateral ACL tear was lower ( P <0.05). There was no significant difference in complication rates ( P = 0.77). Conclusion: Patient-reported outcome measures were similar for patients with BMI above and below 25 kg/m 2, but there is evidence that obese patients have lower IKDC scores. There is a consistent association between overweight status and developing arthritis among patients having an ACL reconstruction. Overweight and obese patients have a lower risk of revision ACL reconstruction and contralateral ACL tear. There is insufficient data to make any conclusions regarding mechanism of injury or complications. More research is needed to better understand what is the appropriate counsel and treatment for overweight or obese patients with ACL tears. Prospero Registration Number: CRD42017055594.